L(α)-Stable Multi-Derivative GLM. Issue 4 (December 2015) - Okuonghae, R. I.; Ikhile, M. N. O.
This paper considers multi-derivative general linear methods and thus presents some second and third derivative general linear methods of orders 5, 7 and 10 in its output methods for computing the solution of stiff initial value problems in ordinary differential equations. The methods derived which is of a simple output structure possesses the special property of Runge-Kutta stability.